Who’s a pretty bird? Predicting the traded abundance of bird species in Australian online pet trade - Katherine G. W. Hill; Oliver C. Stringham; Stephanie Moncayo; Adam Toomes; Jonathan J. Tyler; Phillip Cassey; Steven Delean (Biological Invasions, 2024)

Integrating resource memory and cue-based territoriality to simulate movement dynamics: a process-explicit and pattern-oriented approach - Meryl Theng; Thomas A.A. Prowse; Steven Delean; Phillip Cassey; Chloe Bracis (Ecological Modelling, 2024)

Confronting spatial capture–recapture models with realistic animal movement simulations - Meryl Theng; Cyril Milleret; Chloe Bracis; Phillip Cassey; Steven Delean (Ecology, 2022)
Spatial capture–recapture (SCR) models have emerged as a robust method to estimate the population density of mobile animals. However, model evaluation has generally been based on data simulated from simplified representations of animal space use. Here, we generated data from animal movement simulated from a mechanistic individual‐based model, in which movement emerges from the individual's response to a changing environment (i.e., from the bottom‐up), driven by key ecological processes (e.g., resource memory and territoriality). We drew individual detection data from simulated movement trajectories and fitted detection data sets to a basic, resource selection and transience SCR model, as well as their variants accounting for resource‐driven heterogeneity in density and detectability. Across all SCR models, abundance estimates were robust to multiple, but low‐degree violations of the specified movement processes (e.g., resource selection). SCR models also successfully captured the positive effect of resource quality on density. However, covariate models failed to capture the finer scale effect of resource quality on detectability and space use, which may be a consequence of the low temporal resolution of SCR data sets and/or model misspecification. We show that home‐range size is challenging to infer from the scale parameter alone, compounded by reliance on conventional measures of “true” home‐range size that are highly sensitive to sampling regime. Additionally, we found the transience model challenging to fit, probably due to data sparsity and violation of the assumption of normally distributed inter‐occasion movement of activity centers, suggesting that further development of the model is required for general applicability. Our results showed that further integration of complex movement into SCR models may not be necessary for population estimates of abundance when the level of individual heterogeneity induced by the underlying movement process is low, but appears warranted in terms of accurately revealing finer scale patterns of ecological and movement processes. Further investigation into whether this holds true in populations with other types of realistic movement characteristics is merited. Our study provides a framework to generate realistic SCR data sets to develop and evaluate more complex movement processes in SCR models.

Meta-analysis reveals that resting metabolic rate is not consistently related to fitness and performance in animals - Pieter A. Arnold; Steven Delean; Phillip Cassey; Craig R. White (Journal of Comparative Physiology B, 2021)

Phototactic tails: Evolution and molecular basis of a novel sensory trait in sea snakes - Jenna M. Crowe‐Riddell; Bruno F. Simões; Julian C. Partridge; David M. Hunt; Steven Delean; Julian G. Schwerdt; James Breen; Alastair Ludington; David J. Gower; Kate L. Sanders (Molecular Ecology, 2019)
Dermal phototaxis has been reported in a few aquatic vertebrate lineages spanning fish, amphibians and reptiles. These taxa respond to light on the skin of their elongate hind‐bodies and tails by withdrawing under cover to avoid detection by predators. Here, we investigated tail phototaxis in sea snakes (Hydrophiinae), the only reptiles reported to exhibit this sensory behaviour. We conducted behavioural tests in 17 wild‐caught sea snakes of eight species by illuminating the dorsal surface of the tail and midbody skin using cold white, violet, blue, green and red light. Our results confirmed phototactic tail withdrawal in the previously studied Aipysurus laevis , revealed this trait for the first time in A. duboisii and A. tenuis , and suggested that tail photoreceptors have peak spectral sensitivities between blue and green light (457–514 nm). Based on these results, and an absence of photoresponses in five Aipysurus and Hydrophis species, we tentatively infer that tail phototaxis evolved in the ancestor of a clade of six Aipysurus species (comprising 10% of all sea snakes). Quantifying tail damage, we found that the probability of sustaining tail injuries was not influenced by tail phototactic ability in snakes. Gene profiling showed that transcriptomes of both tail skin and body skin lacked visual opsins but contained melanopsin ( opn4x ) in addition to key genes of the retinal regeneration and phototransduction cascades. This work suggests that a nonvisual photoreceptor (e.g., Gq rhabdomeric) signalling pathway underlies tail phototaxis, and provides candidate gene targets for future studies of this unusual sensory innovation in reptiles.

On the island biogeography of aliens: a global analysis of the richness of plant and bird species on oceanic islands - Tim M. Blackburn; Steven Delean; Petr Pyšek; Phillip Cassey (Global Ecology and Biogeography, 2016)
Aim (1) To characterize the relationship(s) between species richness and area for alien plant and bird species on islands, and to identify commonalities and differences in those relationships for these different taxa, and between alien and native species; (2) to test whether area per se, native species richness or human factors related to area is the primary determinant of alien species richness; and (3) to explore the effects on alien island biogeography of isolation, productivity and the time since first European landfall. Location Islands around the world. Methods We used structural equation models ( SEMs ; supported by generalized linear models) to interrogate data on the alien and native species richness of birds and plants on islands. Results Alien plant and bird species richness were both strongly correlated with island area, with similar slopes on logarithmic axes. SEMs for both plants and birds revealed positive direct effects of native species richness and human population size, and positive indirect effects of area, on alien species richness. The models also identified indirect effects of temperature (positive) and isolation (negative) on alien species richness. Native plant and bird species richness were both predicted by direct effects of area (positive), temperature (positive) and isolation (negative). However, native plant richness was the only direct predictor of native bird species richness, and the strongest direct predictor of alien bird species richness, for islands with both plant and bird richness data. Main conclusions Our analyses recover the species–area, species–isolation and productivity relationships in native richness. Alien species richness was most strongly related to native species richness, with additional effects of human population size. Human population size most likely determines the number of alien species that arrive on an island, while the effect of native species richness may be driven by the influence of habitat heterogeneity on the likelihood that those populations persist (establishment success).

Reconstructing climate–growth relations from the teeth of a marine mammal - Talia A. Wittmann; Christopher Izzo; Zoë A. Doubleday; Jane McKenzie; Steven Delean; Bronwyn M. Gillanders (Marine Biology, 2016)

Density dependence: an ecological Tower of Babel - Salvador Herrando-Pérez; Steven Delean; Barry W. Brook; Corey J. A. Bradshaw (Oecologia, 2012)

Managed relocation as an adaptation strategy for mitigating climate change threats to the persistence of an endangered lizard - Damien A. Fordham; Michael J. Watts; Steven Delean; Brook W. Brook; Lee M.B. Heard; C.M. Bull (Global Change Biology, 2012)
The distributional ranges of many species are contracting with habitat conversion and climate change. For vertebrates, informed strategies for translocations are an essential option for decisions about their conservation management. The pygmy bluetongue lizard, Tiliqua adelaidensis , is an endangered reptile with a highly restricted distribution, known from only a small number of natural grassland fragments in South Australia. Land‐use changes over the last century have converted perennial native grasslands into croplands, pastures and urban areas, causing substantial contraction of the species' range due to loss of essential habitat. Indeed, the species was thought to be extinct until its rediscovery in 1992. We develop coupled‐models that link habitat suitability with stochastic demographic processes to estimate extinction risk and to explore the efficacy of potential climate adaptation options. These coupled‐models offer improvements over simple bioclimatic envelope models for estimating the impacts of climate change on persistence probability. Applying this coupled‐model approach to T. adelaidensis , we show that: (i) climate‐driven changes will adversely impact the expected minimum abundance of populations and could cause extinction without management intervention, (ii) adding artificial burrows might enhance local population density, however, without targeted translocations this measure has a limited effect on extinction risk, (iii) managed relocations are critical for safeguarding lizard population persistence, as a sole or joint action and (iv) where to source and where to relocate animals in a program of translocations depends on the velocity, extent and nonlinearities in rates of climate‐induced habitat change. These results underscore the need to consider managed relocations as part of any multifaceted plan to compensate the effects of habitat loss or shifting environmental conditions on species with low dispersal capacity. More broadly, we provide the first step towards a more comprehensive framework for integrating extinction risk, managed relocations and climate change information into range‐wide conservation management.

Decoupling of component and ensemble density feedbacks in birds and mammals - Salvador Herrando-Pérez; Steven Delean; Barry W. Brook; Corey J. A. Bradshaw (Ecology, 2012)
A component density feedback represents the effect of change in population size on single demographic rates, whereas an ensemble density feedback captures that effect on the overall growth rate of a population. Given that a population's growth rate is a synthesis of the interplay of all demographic rates operating in a population, we test the hypothesis that the strength of ensemble density feedback must augment with increasing strength of component density feedback, using long‐term censuses of population size, fertility, and survival rates of 109 bird and mammal populations (97 species). We found that compensatory and depensatory component feedbacks were common (each detected in ∼50% of the demographic rates). However, component feedback strength only explained

Climate and maternal effects modify sex ratios in a weakly dimorphic marsupial - Steven Delean; Glenn De’ath; Helene Marsh (Behavioral Ecology and Sociobiology, 2009)